Orthopedic surgeon-scientist representation is low among National Institutes of Health grants for rotator cuff research - Nareena Imam, BA; Suleiman Y. Sudah, MD; Joseph E. Manzi, MD; David S. Constantinescu, MD; Allen D. Nicholson, MD; Mariano E. Menendez, MD (JSES International, 2024)
Background: The purpose of this study is to characterize National Institutes of Health (NIH) funding for rotator cuff research and evaluate the impact of orthopedic surgeons on this portfolio. Methods: The NIH’s Research Portfolio Online Reporting Tools Expenditures and Results database was queried for “rotator cuff repair” or “rotator cuff tear” from the 2011 to 2021 fiscal years. Compound annual growth rates were calculated and grants were categorized by basic, clinical, or translational research. Funding totals were compared by Principal Investigator (PI) and grant characteristics. Results: A total of 52 grants were awarded to 38 PIs between 2011 and 2021, totaling $40,156,859. Annual NIH funding for rotator cuff tear and rotator cuff repair increased by a Compound annual growth rate of 11.0% from 2011 to 2021, compared to 3.4% for the total NIH budget. Orthopedic surgeon-scientists received $9,208,212 (22.9%), most commonly through R01 (80.5%) and K08 (7.1%) mechanisms. No significant difference in funding was found by PI sex (P = .332), degree (P = .460), academic rank (P = .118), or researcher type (P = .227). Professors had a higher h-index than associate and assistant professors (P = .001). Orthopedic surgeon-scientists had a higher h-index (mean 36.3 ± 9.4) compared to clinician-scientists (mean 8.0 ± 1.4) and research-scientists (35.5 ± 40.7) (P = .044). Clinical topics receiving the highest funding were rehabilitation (23.9%), diagnosis, (22.3%) and surgical technique (14.8%). Orthopedic surgeon-scientists acquired funding for diagnosis (57.1%), rehabilitation (17.0%), and surgical technique (14.5%). Discussion: While NIH funding for rotator cuff research is growing, orthopedic surgeon representation is low. Future studies should evaluate barriers to obtaining funding for orthopedic surgeon-scientists.